The Impact of Artificial Intelligence on Digital Employee Engagement - Dixit, Abhilasha; Jha, Rimjhim; Baber, Ruturaj; Baber, Prerana (Prabandhan: Indian Journal of Management, 2024)
Purpose : This study aimed to investigate the impact of artificial intelligence (AI) on digital employee engagement, focusing on the roles of job autonomy and digital learning orientation. It sought to understand how these factors influenced employee engagement in a digital environment and the extent to which the meaningfulness of work mediated these relationships. Design/Methodology/Approach : Data were collected from 527 individuals performing administrative jobs in the private service sector. The study utilized partial least squares structural equation modeling (PLS-SEM) to test the proposed relationships among job autonomy, digital learning orientation, and digital employee engagement with mediation of meaningfulness of work. Findings : The findings indicated that job autonomy and digital learning orientation significantly and positively predicted digital employee engagement. However, the meaningfulness of work did not mediate the relationship between job autonomy, digital learning orientation, and digital employee engagement. The results of this study found that there was no significant relationship between the meaningfulness of work and digital employee engagement. This study also found that when the employees used digital tools, they often experienced feelings of loneliness and insecurity. Practical Implications : The study suggested that the organization’s role should always be focused on promoting digital tools. Organizations should emphasize enhancing job autonomy and encourage employees to engage in digital learning orientation, boosting digital employee engagement in the workplace. Originality/Value : This study contributed to the literature considering the role of AI applications that directly influenced digital employee engagement by addressing the significant roles of job autonomy and digital learning orientation. It also emphasized the need for future research to explore the impact of the meaningfulness of work and the dependence on digital tools for employee performance.